Peran job autonomy terhadap work engagement pada karyawan - Suryowibowo, Kuntho; Syakarofath, Nandy Agustin (Universitas Muhammadiyah Malang, 2024)
Work engagement refers to the positive feelings employees have towards their tasks, characterized by full awarenessduring work and perseverance in the face of challenges. Job autonomy involves how employees organize their work, setsuccess targets, make decisions, and choose methods provided by the company. This research aims to determine theimpact of job autonomy on employee work engagement. It employs a causal-comparative research method. The study’spopulation consists of employees, with a sample of 384 participants selected using purposive sampling techniques. Dataanalysis was conducted using simple linear regression to examine the relationship between the work autonomy variableand the work engagement variable. The results indicate a significant influence of work autonomy on work engagement,with a p-value of p < 0.05.